2006
DOI: 10.1080/00365540600617058
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila pneumonia: Specific mRNA in aorta ascendens in patients undergoing coronary artery by-pass grafting

Abstract: The objective of this prospective study was to investigate if Chlamydophila pneumoniae (Cp)-specific DNA and mRNA are present in tissue samples from the wall of aorta ascendens in patients undergoing by-pass surgery for coronary artery disease (CAD) that includes stable angina pectoris (SAP, 25 patients) and acute coronary syndrome (ACS, 19 patients). Viable Cp was detected in 8/44 (18%) patients using reversed transcriptase PCR (RT-PCR) against bacterial mRNA with detection of cDNA using real-time PCR against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…After primary infection, the obligate intracellular bacteria can persist in the host (2,3). Persisting C. pneumoniae are frequently found in the respiratory tract (4 -6) or in atherosclerotic blood vessels (7)(8)(9)(10)(11) and therefore represent a potential risk factor for chronic inflammatory lung diseases (12)(13)(14) or for atherosclerosis (15). It is assumed that C. pneumoniae disseminate from the respiratory tract via infected phagocytes (16,17), which are found to contain C. pneumoniae even in healthy volunteers (18 -20).…”
mentioning
confidence: 99%
“…After primary infection, the obligate intracellular bacteria can persist in the host (2,3). Persisting C. pneumoniae are frequently found in the respiratory tract (4 -6) or in atherosclerotic blood vessels (7)(8)(9)(10)(11) and therefore represent a potential risk factor for chronic inflammatory lung diseases (12)(13)(14) or for atherosclerosis (15). It is assumed that C. pneumoniae disseminate from the respiratory tract via infected phagocytes (16,17), which are found to contain C. pneumoniae even in healthy volunteers (18 -20).…”
mentioning
confidence: 99%
“…Only a few studies have succeeded in isolating C. pneumoniae from atherosclerotic tissue [9,40]. Metabolically active, replicating bacteria can also be demonstrated by the presence of bacterial mRNA as has been done in a previous study of ours in which mRNA was demonstrated in biopsies of the wall of aorta ascendens at the site of the proximal anastomosis of the vein graft in patients undergoing CAGB [19]. Detection rates of C. pneumoniae mRNA are generally lower compared with detection rates of C. pneumoniae DNA, probably partly because mRNA is more susceptible to degradation than DNA and partly because the bacteria present in calcified and disease-altered tissue may have entered a persistent and non-replicative state.…”
Section: Discussionmentioning
confidence: 75%
“…DNA and cDNA samples were subjected to real-time PCR, amplifying a fragment of the C. pneumoniae ompA gene [22] as has previously been described [19]. Control samples of a known concentration were included in each run to verify PCR reproducibility by checking for differences in Ct values.…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…In aorta, Cp antigens were found in 100% in stenotic aortic valves [24], 33% -100% in atherosclerotic aortas [25,26]. Cp DNA was detected in ascending atherosclerotic aortas in 30% and 50% of cases using real-time PCR and nested PCR, respectively [27]. However, in 148 thoracic and abdominal aortic dissections, real-time PCR (using the Taqman system) was negative for Cp in all cases [28].…”
Section: Discussionmentioning
confidence: 99%